Neuroanatomy of Neurogenic Shock - Nalliah, Samantha; Beltran, Mariana; Mulihano, Alfredi; Janjua, Tariq; Moscote-Salazar, Luis Rafael; Agrawal, Amit (Indian Journal of Neurotrauma, 2025)
Neurogenic shock is thus defined as autonomic failure, leading to hypotension, bradycardia, and metabolic vasodilation. The primary pathology lies in the cessation of the sympathetic outflow following the spinal or brain stem injury insult. Thus, an understanding of the neuroanatomic substrate of neurogenic shock's pathophysiology is a prerequisite for a successful approach to diagnosis and therapy. Therefore, this narrative review will comprehensively discuss the neuroanatomic structures involved in the pathology of neurogenic shock, emphasizing their functional significance in the context of the impairment consequences.
Keywords: neurogenic shock; autonomic failure; hypotension; bradycardia; sympathetic outflow; spinal cord injury; pathophysiology; autonomic nervous system